The common-sense assessment of sustainability - Camocho, David (2021)
ABSTRACT: Products claiming sustainability benefits have been spreading all over the world in response, manly, to the consumer’s behavior change towards a healthier and more sustainable way of life. However, what guarantee do consumers have that the products they are consuming are in fact more sustainable? Apart from certified products, the consumer believes in a common-sense assessment of sustainability supported in part by self-declarations and allegations from designers, producers, and retailers focusing only in few aspects of the life cycle, and in some cases, misleading consumers through greenwashing approaches. This paper is part of a Ph.D. research aiming to support a transition to circular economy and sustainability through design. The authors explore in this article the consumer perceptions of sustainability in products and communication strategies adopted. The results will support the development of guidelines to promote a more effective design practice for the development of sustainable and circular economy-based products.